Using mobile phones for vocabulary acquisition in an ESL classroom / Pauline Georgina Priya Hebert Sundram - Pauline Georgina Priya, Hebert Sundram (2017)
The importance of dictionaries in language learning and the usage of mobile phone in this digital era is indisputable. The emergence of mobile phone application dictionary has noticeably influenced the way students learn English as a Second Language (ESL). This study examines the ESL learners’ use of mobile phone in vocabulary acquisition and their perception of learning vocabulary using mobile phone. The study involved 30 intermediate level students studying the Intensive English Program (IEP) in Segi University, Kota Damansara. The students who participated in this study are from China and Middle East. Data for this study was collected through tests, essays, questionnaire and interview. Data obtained from the tests and questionnaires were analyzed using the SPSS software in order to determine the effectiveness of mobile phone dictionary application for vocabulary acquisition and to identify students’ preferences in using mobile phone in learning English as a second language. The data collected through essays and interviews were used to triangulate and strengthen the findings. The findings show that mobile technology particularly the usage of mobile application dictionary contributes towards the vocabulary acquisition of ESL learners. They also show that students have positive preferences towards using mobile phones in learning new vocabularies. The study also displays some of the limitations in utilizing of the mobile application dictionary in vocabulary acquisition for language learners.